Crossbreeding East African Highland Bananas: Lessons Learnt Relevant to the Botany of the Crop After 21 Years of Genetic Enhancement - Batte, Michael; Swennen, Rony; Uwimana, Brigitte; Akech, Violet; Brown, Allan; Tumuhimbise, Robooni; Hovmalm, Helena Persson; Geleta, Mulatu; Ortiz, Rodomiro (Frontiers in Plant Science, 2019)
East African highland bananas (EAHB) were regarded as sterile. Their screening for female fertility with ‘Calcutta 4’ as male parent revealed that 37 EAHB were fertile. This was the foundation for establishment of the EAHB crossbreeding programs of the International Institute of Tropical Agriculture (IITA) and the National Agricultural Research Organization (NARO) in Uganda in the mid-1990s. The aim of this study was to assess the progress and efficiency of the EAHB breeding program at IITA, Sendusu in Uganda. Data on pollinations, seeds generated and germinated, plus hybrids selected since 1995 to 2015 were collected. Pollination success and seed germination percentages for different cross combinations were calculated and analyzed using R-software version 3.4.1. The months of pollination were not significantly different (P = 0.501) for pollination success. Musa acuminata subsp. malaccensis accession 250 had the highest pollination success (66.8%), followed by cultivar ‘Rose’ (66.6%) among the diploid males. Twenty-five EAHB out of 41 studied for female fertility produced up to 305 seeds per pollinated bunch, and were therefore deemed fertile. The percentage of seed germination varied among crosses: 26% for 2x  4x, 22.8% for 2x  2x, 11.1% for 3x  2x and 7.4% for 4x  2x. Twenty-seven NARITA hybrids (mostly secondary triploids ensuing from the 4x  2x) were selected for further evaluation in the East African region. One so far –‘NARITA 7’– was officially released to farmers in Uganda. It was concluded that, pollination of EAHB is possible throughout the year. Musa acuminata subsp. malaccensis accession 250 and cultivar ‘Rose’ were recommended for screening female fertility. Further research on pollination conditions and optimization of embryo culture protocols should be done to boost seed set and embryo germination, respectively. DNA marker-aided selection is needed in addition to more research in floral biology and seed germination in order to increase the efficiency of the EAHB breeding program.